You are on page 1of 11

37

PDF created with pdfFactory Pro trial version www.pdffactory.com

Ft j FS W

F
S
S

()2

()2

f (x) = x 2

Sin x
1
X
-1

01.
f(x) x a f(x) f(x) x=a
lim f ( x ) = A
x a

02.
.

1 f(a)
2 lim f ( x )
3 lim f ( x ) f(a) f xa
a. f
x a

x a

PDF created with pdfFactory Pro trial version www.pdffactory.com

b. f f

lim f ( x ) lim+ f ( x )
x a

x a

lim f ( x ) lim+ f ( x ) f(a)


x a

x a

01.

02.
f ( x ) f (a )
f (a + h) f (a )
lim
f(x)
x a
h0
xa
h
xa f(x) xa f(x) f`(x) f(x)

f ( x + h) f ( x )
f ( x + h) f ( x )
lim
. f`(x) lim
h0
h0
( x + h) x
x
. f(x) f`(a) lim

C.
s(m)

f(x)

t(sec)

v(m/s)

f ' (x)

t(sec)

a (m / s 2 )
f ' ' ( x)

t(sec)
x

PDF created with pdfFactory Pro trial version www.pdffactory.com


01.
dx n
nx n 1
dx
dc
B. c

dx
. n

dn x
1
dx n
1 1 1

xn
. n

dx
dx
n
nn x n 1
BC rQ

dx r
r x r 1 rR
dx

02.
. f(x) g(x) f(x)+g(x)
d
df ( x ) dg ( x )
f(x)+g(x)
+
dx
dx
dx
B. f(x) c
d
df ( x )
(cf ( x )) c
dx
dx
C. f(x) g(x)
d
df ( x ) dg ( x )
( f ( x ) g ( x ))

dx
dx
dx
D. f(x) g(x)
d
dg ( x )
df ( x )
( f ( x ) g ( x )) f(x)(
)+
) g ( x)
dx
dx
dx
E. f(x) g(x)
f ( x)
d

dx
g( x)

g ( x)

df ( x )
dg ( x )
f ( x)
dx
dx
( g ( x )) 2

03.
f(x) g(y) gf
dg ( y )
d
df ( x )
gfx
yf(x)
gf`(x)g`(f(x))
dx
dy
dx

PDF created with pdfFactory Pro trial version www.pdffactory.com


01.
f ( x ) f (a )
xa
x a
xa
a. f(x)f(a) f`(x)

. lim

b. f(x)f(a) f`(x)

c. f(x)f(a) f`(x) f(x) xa

02.
A. f`(a)0 a
B. f(x)
C. f(x)
03.
.
f(x) P yf(x)a,f(a)
f(x) xa a,f(a)
f(x) xa

f(x)f(x)

PDF created with pdfFactory Pro trial version www.pdffactory.com

a. xa yf(x)a,f(a) (a,f(a))
a f`(x) xa f``(a)0
b. xa f``(a)0
C.
a. a xa f(x) xa f(x)(a,f(a)) f(x)

b. F``(a)0 xa
f(x) f`(x)/ f``(x)0
04.
.
L P

.
f(x) yax+b y=f(x)
f ( x)
f ( x)
b lim ( f ( x ) ax ) a lim
b lim ( f ( x ) ax )
x

x
x
x
pf1. yax+b yf(x)

a lim

lim

f ( x ) ax b
a2 +1

lim

f ( x ) ax b

a2 +1

lim f ( x ) ax b lim f ( x ) ax b
x

2. x x 1
0

f ( x)
x
a f ( x ) ax b
x
b

f (x)
b
a lim f ( x ) ax b
x
x
x x
( x )
( x )

0 lim

PDF created with pdfFactory Pro trial version www.pdffactory.com

lim f ( x ) ax b
x

f ( x)
b
f ( x)
b
a lim (
a )
x
x
x
x
x
x
( x )
( x )

lim

f ( x)
f ( x)
a lim
a
x

a
a
( x )
( x )

lim

3. lim f ( x ) ax b lim ( f ( x ) ax b) lim ( f ( x ) ax ) b


x

05.
.
a. f`(a)0 a
b. f(x)
c. f(x)
B.
a. x y
b.
c.
d.
e.

01.
.
.
.
.

PDF created with pdfFactory Pro trial version www.pdffactory.com

x1 y1 1
1
.(x 1 ,y 1 )B(x 2 ,y 2 )C(x 3 ,y 3 )
x2 y 2 1
2
x 3 y3 1
F.a ABC

1
1
1
ab sin C bc sin A ca sin B S ( S a)( S b)(S c )
2
2
2

AB c BC a CA bS
G. OA a OB b a ABC

1
2

1
(a+b+c)
2
2

a b ( a b) 2

02.

1 (a,0)(b,0) n

y = f (x )

x=a

M 1 M 2
M n U n
m1 m2 mn
Ln
m i f(x)

x =b

ba

i (b a )
(i 1)(b a )
a +
,a +
n
n

i f(x)

y = f (x )

x=a

Ln U n

x =b

lim Ln lim U n lim Ln lim U n


n

03.
. a n

PDF created with pdfFactory Pro trial version www.pdffactory.com

a n lim an = a n n
n

B.

C. a n bn liman =a lim bn = b
n

a. a n + bn a + b
lim ( a n + b n ) = a + b lim a n + lim bn
n

b. a n bn a b
lim (an bn ) = a b lim a n lim bn

c. c c a n ca
lim (can ) = ca = c lim a n
n

d. a n b n ab
lim (a nbn ) = ab = liman lim bn
n

e. b 0

an
a

b
bn

an
an a lim
= = n
n b
b lim bn
n
lim

D. a n bn lim a n = a lim bn = b a n bn
n

a b liman lim bn
n

01.
A.n [a, b]
B. i, i = 1,2,3,..., n
i (b a )
(i 1)(b a )
m i M i a +
,a +

n
n

Ln =

ba
(m1 + m2 + ... + mn )
n

PDF created with pdfFactory Pro trial version www.pdffactory.com

U n =

ba
( M 1 + M 2 + ... + M n )
n

C. lim Ln lim U n lim Ln lim U n S S f (x ) [ a, b ]


n

b
a

f ( x )dx a, b

02.
f (x ) [ a, b ][ a, b ] n
f (x ) Ln U n lim Ln lim U n
n

f (x ) [ a, b ] f (x ) [ a, b ]
03.
b

A. ( f ( x ) + g ( x ))dx = f ( x )dx + g ( x )dx


b

B. c f ( x )dx = c f ( x )dx
C.
f(x) [a, b]

b
a

f ( x )dx = [yf(x)xaxb x x

]
D.
a.

b.

a
a
b
a

f ( x )dx = 0
a

f ( x )dx = f ( x )dx
b

04.
A. f(x) g(x) g`(x)f(x)f(x) g(x)
g(x) f(x)

B.
g(x) f(x) g(x)+c (c ) f(x)

C.f(x)() f ( x )dx g(x) f(x)

PDF created with pdfFactory Pro trial version www.pdffactory.com

f ( x )dx =g(x)+c

05.
A. f(x)[a,b][a,b] c
lim f ( x ) = f (c ) g(x) f(x)
x c

b
a

f ( x )dx = g (b) g (a )

B. g (b) g ( a) g ( x ) a
b

g(x) f(x) f ( x )dx = g ( x ) a g (b) g ( a)


b

Hall A. R. 86
841
842

http://episte.math.ntu.edu.tw/entries/en_approximation/index.html

http://episte.math.ntu.edu.tw/entries/en_calculus_e_his/index.html

http://episte.math.ntu.edu.tw/entries/en_continuity/index.html

http://episte.math.ntu.edu.tw/entries/en_dif_equation/index.html

http://episte.math.ntu.edu.tw/entries/en_ftc/index.html

PDF created with pdfFactory Pro trial version www.pdffactory.com